The chemical physics of food (Blackwell Pub., 2006)
This book demonstrates a chemical physics approach to food. Combining the applications of chemical and physical methods with the quantitative consideration of data, the book covers major materials such as emulsions, starches, powders and granular materials, gels, and gluten, and also examines water transport and dynamics in food. The book is of interest to those involved in research into food structure, including food scientists, food technologists, food chemists, and physicists